Arabidopsis thaliana expressing PbBSMT, a gene encoding a SABATH‐type methyltransferase from the plant pathogenic protist Plasmodiophora brassicae, show leaf chlorosis and altered host susceptibility. (25th April 2018) - Bulman, S.; Richter, F.; Marschollek, S.; Benade, F.; Jülke, S.; Ludwig‐Müller, J.
Abstract: The plant pathogenic protist Plasmodiophora brassicae causes clubroot disease of Brassicaceae. This biotrophic organism can down‐regulate plant defence responses. The previously characterised P. brassicae PbBSMT methyltransferase has substrate specificity for salicylic, benzoic and anthranilic acids. We therefore propose a role for the methylation of SA in attenuating plant defence response in infected roots as a novel strategy for intracellular parasitism. We overexpressed PbBSMT under the control of an inducible promoter in Arabidopsis thaliana and performed physiological, molecular and phytopathological analyses with the transgenic plants under control and induced conditions in comparison to the wild type. Upon induction, transcription of PbBSMT was associated with: (1) strong leaf phenotypes from anthocyanin accumulation and chlorosis followed by browning; (2) increased plant susceptibility after infection with P. brassicae that was manifested as more yellow leaves and reduced growth of upper plant parts; and (3) induced transgenic plants were not able to support large galls and had a brownish appearance of some clubs. Microarray data indicated that chlorophyll loss was accompanied by reduced transcription of genes involved in photosynthesis, while genes encoding glucose metabolism, mitochondrial functions and cell wall synthesis were up‐regulated. Our results indicate a role for PbBSMT in attenuation of host defence responses in the roots by metabolising a plant defence signal.